Adaptability of performance to different contextual constraints as a predictor of development and success in competitive football: A systematic review - He, Q.; Araújo, D.; Davids, K.; Kee, Y. H.; Komar, J. (Movement & Sport Sciences - Science & Motricité, 2023)
This systematic review organizes the literature regarding the influence of contextual constraints on football match action profiles, in order to inform better practice when utilized a data-informed approach towards identifying and predicting high performing football players. Furthermore, the validity of examining "on-ball" match actions in competitive matches as an indicator of performance was also investigated. Based on the studies reviewed, task and environmental constraints were highlighted to be significantly influential on match actions performed, which suggests that recruitment strategies may be more successful if there were a greater emphasis on identifying players that best fit the constraints unique to the team, rather than recruiting the "best" player in the position. Additionally, the ability to adapt and successfully produce goal-directed behaviour in a variety of contexts may therefore be indicative of future high performance. Results from existing studies suggest that match actions performed in competitive matches can significantly distinguish between higher and lower performing teams or individuals. However, given the largely retrospective study designs of existing studies, a shift towards prospective study designs utilizing machine learning or statistical modelling is proposed to increase the practical applicability of theoretical findings.